2019
DOI: 10.1038/s41467-019-12976-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of stem N2O exchange follow the physiological activity of boreal trees

Abstract: The role of trees in the nitrous oxide (N2O) balance of boreal forests has been neglected despite evidence suggesting their substantial contribution. We measured seasonal changes in N2O fluxes from soil and stems of boreal trees in Finland, showing clear seasonality in stem N2O flux following tree physiological activity, particularly processes of CO2 uptake and release. Stem N2O emissions peak during the vegetation season, decrease rapidly in October, and remain low but significant to the annual totals during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 60 publications
1
53
1
Order By: Relevance
“…Likewise, full-year investigations of gas emissions might change the results. For instance, Machacova et al 47 found a clear N 2 O emission peak from stems of boreal trees during the vegetation season/summer while there was no effect of soil water content on tree N 2 O fluxes in the vegetation season.…”
Section: Main Controllers Of Ch 4 and N 2 O Fluxes Methane Is Producmentioning
confidence: 99%
“…Likewise, full-year investigations of gas emissions might change the results. For instance, Machacova et al 47 found a clear N 2 O emission peak from stems of boreal trees during the vegetation season/summer while there was no effect of soil water content on tree N 2 O fluxes in the vegetation season.…”
Section: Main Controllers Of Ch 4 and N 2 O Fluxes Methane Is Producmentioning
confidence: 99%
“…These methods include both soil and rice plants in the same system [10,18,[59][60][61], making it difficult to evaluate the role of rice plants. However, for other plants with bigger stems (like trees), recent studies have developed separate chambers that help to capture the fluxes of N 2 O by avoiding soil N 2 O emissions [62]. The chamber used for trees cannot be used for crop species, like rice.…”
Section: Why It Is a Challenge To Understand The Role Of Rice Plants mentioning
confidence: 99%
“…Thus, it is likely that a combination of sufficient water availability, sap flow intensity and rising temperatures led to peak stem CH4 emission in our study. Aside from sap flow intensity, stem CO2 emissions could be used as an indicator for respiration and hence indirectly for physiological activity of the tree (Hölttä & Kolari, 2009;Machacova et al, 2019), that may explain stem CH4 emissions (Barba et al, 2017). However, in our study stem CO2 emissions at AW could only explain 1% of all CH4 fluxes larger than 0.1 mg m -2 h -1 (tested with linear models, data not shown).…”
Section: Drained Vs Undrained Alder Forestmentioning
confidence: 56%